Optimum Operation of Makhool Dam - A. Al-Delewy, Abdul-Hadi; A-S. M. Ali, Ahmed; H. Motalib, Riyadh (Journal of Engineering and Sustainable Development, 2005)
In this research, the discrete differential dynamic programming approach is used to find the optimal monthly operation of Makhool Dam by adopting an objective function to minimize the release and storage penalty. The historical inflow data of (480) months (from Oct. 1960 to Sep. 1999) formed the input data to the optimization model. To preserve the logical state of reserve storage, i.e., save minimum operation storage just before the expected start of the effective flood and maximum operation storage at the end of the flood season, a new constraint has been introduced. The new constraint also ensured the smoothness of the resulting optimum rule curves (lower, average, and upper). A simulation model is built accordingly. Besides, the developed optimization model is applied to two hypothetical operation scenarios that represent the extreme cases, namely, two consecutive relatively-wet years and two consecutive relatively-dry years, beside the consideration of the non-existence and existence of Bekhma Dam. The optimum operation policy has shown deficit in satisfying the demands downstream Makhool Dam. The deficiency was noticed during (30) months when Bekhma Dam is not existing and (21) months when Bekhma Dam is operational.